Entorno familiar y su influencia en el rendimiento escolar de los alumnos del 6to grado de nivel primario de la institución educativa "Manuel Arévalo", La Esperanza, 2015. - García Escudero, Yoselín Yemida (2015)
This research was conducted to analyze how the family environment influences the Academic Performance 6th grade students at the secondary level of the S.I. "Manuel Arevalo" district of La Esperanza in 2015. It is considered that the involvement of parents in the educational process is one of the primary factors that can contribute to the process of student learning and development of values in the integral formation of the student. In I.E. "Manuel Arevalo" children with poor school performance, not actively participate in classes, homework not done, a situation that is linked to unfavorable social environment around them, because they do not receive the affection and attention he was found that parents should give their children. The information was obtained by the social tab applied to 25 families, so also a questionnaire to 25 children and 45 parents Sixth Grade Primary Education S.I. "Manuel Arevalo," to what the questionnaire with questions addressed to meet the family environment of children and their parents was developed. The interpretation of the survey results is clear: that the children express that parents do not provide good emotional relationship; the highest percentage of students do not have adequate communication between family members; their parents do not give them affection; most children show that their opinions are not respected; that most children do not fulfill their tasks for lack of emotional relationship, most children are reluctant to participate in class insecurity accept its criteria and some have a docile and full behavior in fear of their teachers and other companions. The result of the questionnaires and social tab, allows to establish that, ultimately, the family environment does influence school performance. The proposal to improve the family environment is extended to the realization of a school for parents, aimed at optimizing school performance of children of school subject of this study.